Cancer Therapy by Catechins Involves Redox Cycling of Copper Ions and Generation of Reactive Oxygen Species - Farhan, Mohd; Khan, Husain; Oves, Mohammad; Al-Harrasi, Ahmed; Rehmani, Nida; Arif, Hussain; Hadi, Sheikh; Ahmad, Aamir (Toxins, 2016)
Catechins, the dietary phytochemicals present in green tea and other beverages, are considered to be potent inducers of apoptosis and cytotoxicity to cancer cells. While it is believed that the antioxidant properties of catechins and related dietary agents may contribute to lowering the risk of cancer induction by impeding oxidative injury to DNA, these properties cannot account for apoptosis induction and chemotherapeutic observations. Catechin (C), epicatechin (EC), epigallocatechin (EGC) and epigallocatechin-3-gallate (EGCG) are the four major constituents of green tea. In this article, using human peripheral lymphocytes and comet assay, we show that C, EC, EGC and EGCG cause cellular DNA breakage and can alternatively switch to a prooxidant action in the presence of transition metals such as copper. The cellular DNA breakage was found to be significantly enhanced in the presence of copper ions. Catechins were found to be effective in providing protection against oxidative stress induced by tertbutylhydroperoxide, as measured by oxidative DNA breakage in lymphocytes. The prooxidant action of catechins involved production of hydroxyl radicals through redox recycling of copper ions. We also determined that catechins, particularly EGCG, inhibit proliferation of breast cancer cell line MDA-MB-231 leading to a prooxidant cell death. Since it is well established that tissue, cellular and serum copper levels are considerably elevated in various malignancies, cancer cells would be more subject to redox cycling between copper ions and catechins to generate reactive oxygen species (ROS) responsible for DNA breakage. Such a copper dependent prooxidant cytotoxic mechanism better explains the anticancer activity and preferential cytotoxicity of dietary phytochemicals against cancer cells.